Reading John Maynard Keynes : a short introduction - Solimano, Andrés (Routledge, 2024)
"This book focuses on understanding the thinking of one of the greatest economist of the 20th century: John Maynard Keynes (JMK) stressing the evolution of his thinking from adherence to the classic Quantity Theory of Money to the development of his own novel theories of unemployment, stagnation and instability in modern capitalism and the need to have active policies to combat these malaises. The author dissects Keynes's three main analytical works that shaped his thinking and policy recommendations: A Tract on Monetary Reform (1923); A Treatise on Money (1930); and The General Theory of Employment, Interest and Money (1936). The book undertakes a direct analysis of the texts of each of these three books themselves, rather than drawing on secondary literature studying what Keynes "wanted to say" according to other authors sympathetic or unsympathetic with Keynes's ideas. It is an ideal text for a reader who wants to know in clear terms the thought of JMK and the historical context in which it evolved and developed. The book will be of significant interest to scholars, students and social researchers in various fields who are often surrounded by excessively technically- oriented books about Keynes that often omit the history of ideas"-- Provided by publisher.
Keywords: Keynes, John Maynard, -- 1883-1946.; Keynesian economics.; Economics -- Philosophy.; elektronické knihy; electronic books